Sleep duration and insulin resistance in individuals without type 2 diabetes: The PPP-Botnia Study. (August 2014) - Pyykkönen, Antti-Jussi; Isomaa, Bo; Pesonen, Anu-Katriina; Eriksson, Johan G.; Groop, Leif; Tuomi, Tiinamaija; Räikkönen, Katri
Abstract Introduction. Both short and long sleep duration may increase risk of type 2 diabetes (diabetes). We studied if short and long sleep durations were associated with insulin resistance (IR) and insulin secretion in individuals without diabetes, and if the associations remained after we excluded individuals who reported more frequent and severe complaints of sleep apnea and insomnia. Participants and methods. An oral glucose tolerance test (OGTT) was performed for 722 adults without diabetes. Indices of IR and insulin secretion were calculated. Sleep duration and complaints of sleep apnea and insomnia were self-reported. Results. In comparison to average sleepers (6–9 h/night), short sleepers (< 6 h/night) had higher 120-min insulin and AUC glucose, and long sleepers (≥ 9 h/night) had higher fasting and 120-min insulin, 120-min glucose, and HOMAIR and lower Insulin Sensitivity Index. After adjusting for confounders and after excluding individuals who reported more frequent and severe complaints of sleep apnea and insomnia, long sleep duration remained significantly associated with IR and insulin secretion. Discussion. Long but not short sleep duration is associated with IR and insulin secretion in individuals without diabetes whether or not accompanied by sleep complaints. Long sleepers may benefit from targeted preventions and interventions that aim at reducing risk of future diabetes.